Profiling and Simultaneous Quantitative Determination of Anthocyanins in Wild Myrtus communis L. Berries from Different Geographical Areas in Sardinia and their Comparative Evaluation. Issue 5 (20th July 2016) - Maldini, Mariateresa; Chessa, Mario; Petretto, Giacomo L.; Montoro, Paola; Rourke, Jonathan P.; Foddai, Marzia; Nicoletti, Marcello; Pintore, Giorgio
Abstract: Introduction: Myrtus communis L. (Myrtaceae) is a self‐seeded shrub, widespread in Sardinia, with anti‐inflammatory, antiseptic, antimicrobial, hypoglycemic and balsamic properties. Its berries, employed for the production of sweet myrtle liqueur, are characterised by a high content of bioactive polyphenols, mainly anthocyanins. Anthocyanin composition is quite specific for vegetables/fruits and can be used as a fingerprint to determine the authenticity, geographical origin and quality of raw materials, products and extracts. Objective: To rapidly analyse and determine anthocyanins in 17 samples of Myrtus communis berries by developing a platform based on the integration of UHPLC–MS/MS quantitative data and multivariate analysis with the aim of extracting the most information possible from the data. Methodology: UHPLC‐ESI‐MS/MS methods, working in positive ion mode, were performed for the detection and determination of target compounds in multiple reaction monitoring (MRM) mode. Optimal chromatographic conditions were achieved using an XSelect HSS T3 column and a gradient elution with 0.1% formic acid in water and 0.1% formic acid in acetonitrile. Principal component analysis (PCA) was applied to the quantitative data to correlate and discriminate 17 geographical collections of Myrtus communis . Results: The developed quantitative method was reliable, sensitive and specific and was successfully applied to the quantification of 17 anthocyanins. Peonidin‐3‐ O ‐glucoside was the most abundant compound in all the extracts investigated. Conclusion: The developed methodology allows the identification of quali‐quantitative differences among M. communis samples and thus defines the quality and value of this raw material for marketed products. Moreover, the reported data have an immediate commercial value due to the current interest in developing antioxidant nutraceuticals from Mediterranean plants, including Sardinian Myrtus communis . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A qualitative and quantitative evaluation of the anthocyanins in Myrtus communis berries collected from wild plants in different areas of Sardinia (Italy) was performed using liquid chromatography‐tandem mass spectrometry methods. In addition, principal component analysis was employed to evaluate differences/similarities between the analyzed extracts. 17 anthocyanins belonging to the classes of cyanidins, delphinidins, malvidins, petunidins, pelargonidins and peonidins were identified. The developed methodology allowed the identification of quali‐quantitative differences among Myrtus communis samples collected from 17 different areas of Sardinia.